The obligation of contractor during defect liability period / Muhamad Hafiz Ahmad Azhar - Ahmad Azhar, Muhamad Hafiz (2014)
This dissertation contains six chapter that explain about the obligation of contractor during defect liability period. Chapter 1 are compilation of general information about my study. This chapter presents the overall content of the whole project writing. It introduces the subject matter, the problems that are purported to solve. The objective is specified with an appropriate research method to achieve them .Chapter 2 are compilation of literature review. This chapter with the overview the common roles of contractor, preparing to start the contract and classification of contractor. In addition, this chapter also tell about the general information of defect liability period, process of defect liability period, case of defect liability period in Malaysia, and term and condition of defect liability period.